The Relationship Between Oxytocin Massage With Public Breast Milk Expenditure - Rostiana, Aros; Karo, Marni Br; Nisa, Hainun (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
The most important time during breastfeeding is the first few days after giving birth. If a mother is assisted properly when she starts breastfeeding, it is likely that the mother will be successful in continuing to breastfeed. The reality on the ground shows that a small expenditure and ejection of breast milk in the first days after giving birth is an obstacle in early breastfeeding. It was stated that mothers who did not breastfeed their babies in the first days of breastfeeding were caused by mothers' anxiety and fear of reduced milk output and mothers' lack of knowledge about the breastfeeding process. Anxiety and fear by causing a decrease in the hormone oxytocin so that breast milk cannot come out immediately after giving birth, the mother finally decides to give formula milk to her baby. If the mother does not know how to deal with a decrease in milk production, one of which is by means of oxytocin massage.